Determination of the Bearing Capacity of Concrete-Filled Steel Tubular Structures Coupled with Dismountable Joints - Semko, P.; Gasii, G. (International Journal of Sustainable Construction Engineering and Technology, 2021)
The analysis method of the bearing capacity of concrete-filled steel tubular structures coupled with dismountable joints is presented (in particular elements with flange joints, and longitudinal ribs joints, and steel coupling joints). With the help of the above way, the curves of the bearing capacity of the dismountable joints are plotted. The comparison was made to determine the most optimal joints from presented.